2020
DOI: 10.1186/s13068-020-1655-9
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen radical based on non-thermal atmospheric pressure plasma alleviates lignin-derived phenolic toxicity in yeast

Abstract: Background: Vanillin is the main byproduct of alkaline-pretreated lignocellulosic biomass during the process of fermentable-sugar production and a potent inhibitor of ethanol production by yeast. Yeast cells are usually exposed to vanillin during the industrial production of bioethanol from lignocellulosic biomass. Therefore, vanillin toxicity represents a major barrier to reducing the cost of bioethanol production. Results: In this study, we analysed the effects of oxygen-radical treatment on vanillin molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 66 publications
1
5
0
Order By: Relevance
“…In this study, irradiation of neutral reactive species resulted in the monooxygenation, dechlorination, and aromatic ring fission of 4-CP. Similarly, in our previous study, we showed that NTAP irradiation results in the hydroxylation, demethylation, decarboxylation, and ring cleavage of the lignin-derived phenolic compound vanillin . Additionally, Shokri et al (2019) indicated that the 4-CP concentration was decreased by NTAP (O 2 and Ar) irradiation and that one major reaction product (2,3-dihydrofuran) was obtained .…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…In this study, irradiation of neutral reactive species resulted in the monooxygenation, dechlorination, and aromatic ring fission of 4-CP. Similarly, in our previous study, we showed that NTAP irradiation results in the hydroxylation, demethylation, decarboxylation, and ring cleavage of the lignin-derived phenolic compound vanillin . Additionally, Shokri et al (2019) indicated that the 4-CP concentration was decreased by NTAP (O 2 and Ar) irradiation and that one major reaction product (2,3-dihydrofuran) was obtained .…”
Section: Discussionsupporting
confidence: 69%
“…Similarly, in our previous study, we showed that NTAP irradiation results in the hydroxylation, demethylation, decarboxylation, and ring cleavage of the lignin-derived phenolic compound vanillin. 32 Additionally, Shokri et al (2019) indicated that the 4-CP concentration was decreased by NTAP (O 2 and Ar) irradiation and that one major reaction product (2,3-dihydrofuran) was obtained. 33 Using Fourier transform infrared spectroscopy and 1 H nuclear magnetic resonance analyses, Asandulesa et al (2013) showed that the aromatic ring of benzyl chloride was cleaved and converted to aliphatic groups via NTAP irradiation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, atmospheric pressure plasmas are of great interest, owing to simple operation (not employing vacuum system), reduced processing cost, and the possibility of the application of plasma to samples which are not compatible with low-pressure conditions [1]- [5]. On the other hand, the fast development of non-equilibrium (also called non-thermal or cold) plasmas in the last two decades has allowed the application of plasma technologies in medicine and agriculture [3], [6]- [10]. In this case, the non-equilibrium nature of the plasma (temperature of electrons is much higher than temperature of gas) allows the creation of reactive species without excessive heat of the gas and treatment of targets which are sensitive to overheating (polymers, plants, tissues, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, the simultaneous presence of sodium and vanillin, known to inhibit the activity of the DNA-dependent protein kinase catalytic subunit, appears to have an opposite effect, resulting in hampered cell proliferation in D. hansenii strains (Figure 2). However, depending on the lignocellulosic biomass composition and pretreatment used, a vast range of vanillin concentrations can be present, from 1-26 mM (Ito et al 2020). Therefore, the effect of higher concentration of vanillin should be further investigated in order to get a better picture about the inhibitory impact of vanillin on D. hansenii strains.…”
Section: Navarrete Et Al 2020a)mentioning
confidence: 99%